An interactive debugging tool for C++ based on dynamic slicing and dicing part I : definition and algorithms - Wichaipanitch, Winai (Frontiers in Engineering Innovation Research, 2003)
The main objective of this work was to develop an interactive debugging tool for C++ programs. The tool that was developed is called C++Debug and it uses program slicing and dicing techniques. The design started by including simple statements first and then expanded to pointers, structures, functions, and classes. In order for C++Debug to be more powerful, dynamic slicing rather than static slicing was chosen. The work includes new algorithms that handle Class, Function, and Pointer in C++. The results of this work are reported in two